2002
DOI: 10.1210/jc.87.5.2352
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Adipogenesis, Peroxisome Proliferator-Activated Receptor-  (PPAR ), and Thyrotropin Receptor by PPAR  Agonist in Human Orbital Preadipocyte Fibroblasts

Abstract: The symptoms and signs of Graves' ophthalmopathy (GO) result from both an accumulation of hydrated hyaluronan in the orbital muscles and connective tissues and an expansion of the orbital adipose tissues. Recent studies have suggested a link between the stimulation of adipogenesis within the orbit in GO and the expression in these tissues of TSH receptor (TSHR), the putative orbital autoantigen. To further investigate this association, we treated orbital fibroblasts from patients with GO with rosiglitazone, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 0 publications
4
85
1
2
Order By: Relevance
“…Recent evidence in experimental animals and in humans has shown that adipocytes and preadipocytes possess TSH receptors (TSHRs), [11][12][13] and that TSH action induces the differentiation of preadipocytes into adipocytes, adipogenesis and, in children, lipolysis. 11,14,15 However, there are no data on the adipose tissue expression of the TSHR gene in conditions such as severe obesity and/or diabetes. Therefore this study was undertaken (1) to assess the separate role of obesity and type 2 diabetes (T2DM ) in the expression of the thyrotropin receptor (TSHR) and thyroid hormone receptor (a1 subunit, TRa1) genes in visceral adipose tissue (VAT) and in subcutaneous adipose tissue (SAT) and (2) to explore the role of metabolic state and weight loss on receptor expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence in experimental animals and in humans has shown that adipocytes and preadipocytes possess TSH receptors (TSHRs), [11][12][13] and that TSH action induces the differentiation of preadipocytes into adipocytes, adipogenesis and, in children, lipolysis. 11,14,15 However, there are no data on the adipose tissue expression of the TSHR gene in conditions such as severe obesity and/or diabetes. Therefore this study was undertaken (1) to assess the separate role of obesity and type 2 diabetes (T2DM ) in the expression of the thyrotropin receptor (TSHR) and thyroid hormone receptor (a1 subunit, TRa1) genes in visceral adipose tissue (VAT) and in subcutaneous adipose tissue (SAT) and (2) to explore the role of metabolic state and weight loss on receptor expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, 17 of the 29 reviewed studies found a positive association between anthropometric measures and serum TSH, and the two longitudinal population-based studies showed a positive association between serum TSH concentration and BMI or body weight (6,31). The plausibility of this association has been discussed and could be mediated by TSH action directly stimulating preadipocyte differentiation, thus inducing adipogenesis (36,37). Another hypothesis is that the association between serum TSH and body weight may be due to leptin (38).…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies have yielded convincing evidence that adipocytes and preadipocytes express TSH receptors (32). The action of TSH on its receptors in fat tissue induces differentiation of preadipocytes into adipocytes, causing stimulation of adipogenesis (33). All of these reciprocal mechanisms suggest that leptin and the thyroid axis maintain a complex and dual relationship and it might be proposed that a 'hypothalamic-pituitarythyroid-adipose axis' exists.…”
Section: Thyroid Nodulementioning
confidence: 99%